Twenty Shades of Italy: An Analysis of its Cultural, Natural, and Dual Tourist Attractions with Implications for Global Tourism Marketing. Issue 5 (20th October 2017) - Manrai, Lalita A.; Manrai, Ajay K.; DeLuca, Joseph
ABSTRACT: Natural and cultural tourism are the two main motivations for international tourists. The country of Italy is recognized for both of these dimensions. To fully understand the tourism characteristics of this geographically diverse and historically rich land, we compare 20 regions of Italy and identify major natural, cultural, and dual (both natural and cultural) tourist attractions as well as the number of tourists across these 20 regions. As far as we know, it is the first study of its kind to analyze tourism in Italy at the regional level. The findings of this research reveal four distinct clusters based on the regions resulting from "high versus low number of attractions" by "high versus low number of tourists." We also analyzed secondary data on region-wise tourist-nights using discriminant analysis. The results showed that the dual (both cultural and natural) attraction sites are the most important in explaining differences in tourism across the different regions of Italy. We discuss implications of the results for global tourism marketing.